THE FORMATION OF UNIVERSAL EDUCATIONAL ACTIONS OF FORMULATING AND SOLVING PROBLEMS IN PRIMARY SCHOOL CHILDREN - Solovyova, Tatiana; Smirnova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article is intended for the organization of the effective intellectual development of junior schoolchildren. For this purpose, the article presents the structure of the universal cognitive actions for formulating and solving problems allowing teachers to manage their forming in the educational process of primary school. The substantial characteristic of each of the structural components built through the analysis of theoretical sources, the pilot study and the standardized observation of the school practice that have been conducted made it possible to describe the criteria, the indicators and the levels of formation of the universal educational actions for formulating and solving problems by primary school children.